A feasibility study on a rapid detection kit for amebiasis patients through salivary IgA - Agnes, Jane M.; Balbastro, Jasmin; Magpantay, Maria Theresa; Naga, Ismael Ansary
A team of Biology students of the University of the Philippines - College of Science, under the guidance of Dr. Windell Rivera PhD, successfully developed an amoebiasis test protocol which instead of the conventional stool or blood samples, uses saliva to detect an amoebiasis infection. The protocol was designed and envisioned to be an amebiasis detection kit which was more accurate, more convenient and faster than any other testing procedure. The potential benefits that could be derived from mass producing and mass distributing the kit to communities most at risk of amebiasis infection cannot be overemphasized. A study to determine market, technical and financial feasibility as well as socio-economic profitability was in order. To characterize the Philippine market, various public hospitals were investigated to determine frequency of lab tests for suspected amebiasis infections; a total of 192,372 examinations were estimated to have been conducted in 2010. Demand projections for the kits for the next five years were made based on the year 2010 lab test estimates. Market shares were estimated to portray possible Profit margins. Equipment, manpower and tooling requirements were determined to know if the available technology was sufficient in mass producing the kits, for which the answer was of the affirmative. Associated costs for such production were also characterized. Upon comparison of the potential sales with all associated costs, it was found out that the production of the kits for commercial distribution is only marginally feasible. Monetary gains are hard to realize due to the small market size. The financial study only confirms that from a business perspective, producing and distributing the kits for the Philippine market is not a profitable venture. To make a profit, either the market should be expanded or the kit's appeal be strengthened by further developing the technology to include detection of other forms of infectious diseases. From the consumer's perspective however, socio-economic benefits are very attractive that the idea of producing amoebiasis detection kits for humanitarian reasons clearly warrant a deeper investigation.